Once-weekly oral islatravir plus lenacapavir: clinical considerations for individualized use - Paolo Fusco; Alessandro Russo (JAIDS Journal of Acquired Immune Deficiency Syndromes, 2026)
Once-weekly oral islatravir plus lenacapavir represents a promising strategy to expand treatment choice for people with HIV (PWH) who prefer oral therapy without daily dosing. Phase 2 findings provide reassuring evidence of maintained virological suppression and support further clinical development. Rather than reflecting shortcomings of early-phase evaluation, the key questions now relate to the regimen’s future clinical use, including its pharmacokinetic and virological forgiveness after delayed or missed doses, optimal hepatitis B virus (HBV) screening, vaccination, and monitoring when switching to a regimen without HBV-active agents, and the clinical relevance of drug–drug interactions in the setting of polypharmacy. Addressing these issues will help inform individualized treatment decisions, counseling, and clinical monitoring as the regimen advances through clinical development and, potentially, into routine clinical practice.